IDENTIFIKASI KEMAMPUAN BERARGUMEN SISWA SMPN 24 GRESIK PADA MATERI PENCEMARAN LINGKUNGAN - Khosiyati, Khosiyati; Tamam, Badrud; Wahyuni, Eva Ari; Sidik, Rahmad Fajar; Rakhmawan, Aditya (Natural Science Education Research, 2023)
The purpose of this study was to determine the level of argumentation skills of the students of SMPN 24 Gresik in Dungus Village, Cerme District, Gresik Regency on environmental material. This study uses a quantitative descriptive method. The population in this study were all students for the 2021/2022 academic year. The sampling technique used in this research is purposive sampling. The research sample used was 32 students. Data was collected using a 10-point essay test, in which each number contained three assessment indicators, namely, evidence and scientific reasons. The results of the research are: 1) The argumentation ability of students on environmental material in class VII is overall good with an average percentage of 81.2%. 2) Identification of the ability to argue students in each aspect of the indicator can be seen that the ability of students to claim is quite good, namely with a value of 89%, in the aspect of the ability to give good answers, namely with a percentage of 78%, while in the aspect of the ability to make scientific reasons it is classified as good with a value percentage 76%